Species Richness of Spermatophyta Plants in Paseban Parks Bangkalan Madura to Develop Discovery Model on the Material Handout Plantae - Rizqiyah, Iffatur; Ngabekti, Sri; Dewi, Nur Kusuma (Journal of Innovative Science Education, 2018)
Handout materials are materials that are Concise and complete. One the innovations of the handout was a handout discovery model of curriculum corresponding to 2013. This research aims to Identify a) species richness of Spermatophyta plants in Paseban parks Bangkalan to develop discovery model on the material handout, b) to test the validity of the handout models of plant discovery Plantae Spermatophyta on learning, c) to test the effectiveness of the handout model of discovery of plant Spermatophyta, d) to test the response of students and teachers against the handout models of plant Spermatophyta discovery. Method development using the method of ADDIE. Results of the study include a) 28 species that comprise the family Cannaceae, Liliaceae, Acanthaceae, Rubiaceae, Agaveaceae, Rubiaceae, Apocynaceae, Palma, Fabeacae, Nygtaginaceae, euphorbiaceae, Cydaceaae, Gnetaceae, Pinaceae and. b) The validity of expert material and expert media an average of  94.92% with very valid criteria c) Effectiveness handouts based on test results of t-test results Showed significant 0:04 Becauseρ value < α 0:05. The experiment has been completed on the class 100%. The percentage of the value of the excellent category of affective on classroom control 85.51% and 90.23% in class experiments. The percentage of psychomotor categories very well at 79.08% control classes and experiments 86.19%, Thus it can be stated that giving a handout models Effectively discovery. d) Response use the handout model of discovery of 95.66% included in the category of very decent.